PENGARUH EFISIENSI BIAYA PERBANKAN DI KAWASAN ASEAN- 5 - Tamitha Intasar Husen (universitas teuku umar, 2017)
Abstract. This study examines determinants of cost efficiency of banking operation in ASEAN-5 region which includes Indonesia, Singapura, Malaysia, the Philippines, and Thailand. By using stochastic frontier analysis (SFA) to 23 commercial banks in the region in the period of 2005-2012, empirical results reveal certain significant relationship of cost efficiency with individual bank characteristic (return on equity, ROE). Based on the time-varying decay method, we conclude that there is an increase in cost efficiency during the period of study. This study also shows that in general, Indonesian banking industry was not operating efficiently. Keywords: ASEAN-5, cost efficiency, banking, SFA, time-varying decay